Prenylflavonoids isolated from Epimedii Herba show inhibition activity against advanced glycation end-products - Nakashima, Keisuke; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi; Fujiwara, Yukio; Nagai, Ryoji; Ikeda, Tsuyoshi (Frontiers in Chemistry, 2024)
Introduction: As inhibitors of advanced glycation end products (AGEs), such as pyridoxamine, significantly inhibit the development of retinopathy and neuropathy in rats with streptozotocin-induced diabetes, treatment with AGE inhibitors is believed to be a potential strategy for the prevention of aging, age-related diseases, and lifestyle-related diseases, including diabetic complications. In the present study, the MeOH extract of Epimedii Herba (EH; aerial parts of Epimedium spp.) was found to inhibit the formation of Nε-(carboxymethyl)lysine (CML) and Nω-(carboxymethyl) arginine (CMA) during the incubation of collagen-derived gelatin with ribose. Materials and methods: EH was purchased from Uchida Wakan-yaku Co., and a MeOH extract was prepared. Several steps of column chromatography purified the extract. Each fraction was tested for inhibitory activity by ELISA using monoclonal antibodies for CML and CMA. Results: After activity-guided fractionation and purification by column chromatography, three new prenylflavonoids [named Koreanoside L (1), Koreanoside E1 (2), and Koreanoside E2 (3)] and 40 known compounds (4–43) were isolated from EH, and their inhibitory effects against CML and CMA formation were tested. Among these, epimedokoreanin B (8), epimedonin E (21), epicornunin B (22), and epicornunin F (24) inhibited the formation of both CML and CMA, with epimedokoreanin B (8) having the most potent inhibitory effect among the isolated compounds. To obtain the structure–activity relationships of 8, the phenolic hydroxy groups of 8 were methylated by trimethylsilyl-diazomethane to afford the partially and completely methylated compounds of 8. Prenyl derivatives of propolis (artepillin C, baccharin, and drupanin) were used in the assay. Discussion: As only 8 showed significant activity among these compounds, the catechol group of the B ring and the two prenyl groups attached to the flavanone skeleton were essential for activity. These data suggest that 8 could prevent the clinical complications of diabetes and age-related diseases by inhibiting AGEs.